PROGRAMA DE QUALIDADE DE VIDA NO TRABALHO: UM ESTUDO DE CASO EM UMA INSTITUIÇÃO FEDERAL DE ENSINO SUPERIOR - Moreira, Ivna Martins Mendonça (2013)
The objective of this study is to develop a proposal for the strategic alignment of the actions of quality of life at work within the UFF. The used methodology was a documental, bibliographic and empirical research, regarding the means, and descriptive and explanatory, regarding the purposes. This research was carried out as a study case, with a qualitative approach and the participation of thirty-six (36) servants. Using the Test of Evolution of Words as the data collection method, completed by the application of the questionnaire, the research concludes that respect , team integration and satisfaction with tasks accomplishment consists in the main focus of servant´s social representation regarding the quality of life at work endorsed by the elements of the peripheral system recognition , routine definition , balance work/personal life and training and qualification . The model Quality of Life at Work from Walton was used as a parameter to the semantic categorization. The interpretative analysis of the answers of the questionnaire indicates that the activities of promotion of the quality of life at work, offered by the Institution, are evaluated in a positive way and the servant non-participation is especially due to the incompatibility of timing and unawareness of schedule. The presented results demonstrate great advance in the administrative aspect of this area and induce to the conclusion, from the servant´s perception, that the activities related to the quality of life at work promoted by the Institution are reaching their goals, in spite of the number of participating servants is still short of ideal.